Occupational therapy on the margins. Issue 2 (3rd July 2017) - Pollard, Nick; Sakellariou, Dikaios
ABSTRACT: This article discusses occupational therapy's pursuit of social concerns through practice with marginalised groups or engaging with diversity. In this article we understand the term marginalisation as referring to people who are socially excluded from the rest of the society in which they live because of some economic, cultural, or social difference. We take the perspective that the experiences of marginalised people offer one means of assessing public health and social cohesion. We also explore the profession's recent literature on social transformation. Occupational therapy's narrow demographic profile and dominance of a Northern discourse are critically discussed in terms of engagement with how the problems of marginalisation, such as health inequality and poverty, impact on occupation. We address some of the problems which arise through professional and organisational power when working with marginalised people. The article concludes with an overview of the complexity of challenges in developing actions to meet diverse needs from a profession that is still growing.